Rekonstruksi Pengaturan Hukum Pidana Terhadap Penangkapan Ikan Secara Melawan Hukum (Illegal Fishing) Berbasis Kepastian Hukum - Latuconsina, Ruswan; Uwiyono, Uwiyono; Sumanto, Listyowati (Sharia Journal and Education Center Publishing, 2025)
This research examines the reconstruction of criminal law regulations against illegal fishing in Maluku waters, focusing on legal certainty. The primary issue addressed is the ineffectiveness of current regulations, specifically Law Number 45 of 2009, in prosecuting intellectual actors and corporations, coupled with weak coordination among law enforcement agencies, leading to rampant fish poaching in the Maluku archipelago. The research employs a normative-empirical legal method with statutory and case approaches. The findings indicate the existence of legal lacunae and disparities in judicial decisions that fail to provide a deterrent effect or comprehensively account for ecological losses. Furthermore, limited monitoring facilities and low legal culture among the community pose significant obstacles. The proposed reconstruction involves revising legal substance to clarify corporate criminal liability, synchronizing specific minimum criminal sanctions, and strengthening law enforcement structures through an integrated coordination center. Through a legal reconstruction based on legal certainty, it is expected to protect Indonesia's maritime sovereignty, preserve fishery ecosystems, and enhance the welfare of fishermen in Maluku Province sustainably.